AB1179-HPR Associations between Occupational Balance and Immunology: Differences in Health Conditions, Employment Status Und Gender. (10th June 2014) - Dür, M.; Steiner, G.; Fialka-Moser, V.; Kautzky-Willer, A.; Stoffer, M.; Prodinger, B.; Dejaco, C.; Smolen, J.; Stamm, T.
Abstract : Background: Occupational therapists are health professionals focusing on activities of daily living as a means, but also as an outcome of therapy. A balance of activities, the so-called "occupational balance", including other occupations than paid work e.g. self-care, household activities, voluntary work and caring for others, is one potential link between "occupations" and "health". There is growing evidence for the interrelations of neurological processes, immunological parameters and psychosocial factors. Objectives: We aimed to compare the associations between occupational balance and immunological parameters of employed and non-employed people with rheumatoid arthritis and healthy controls. Methods: We conducted a quantitative study in people in employable age with rheumatoid arthritis and healthy controls. Demographic data such as gender and employment status was collected. The Occupational Balance-Questionnaire and the SF-36 were used. Additionally, levels of immunological parameters, such as IL-6, IL-8, TNFα, INFα, RF, ACPA and CRP were measured. Descriptive statistics, Spearmen's correlation coefficients and Mann-Whitney U tests were calculated. Results: A total of 208 people (132 patients with rheumatoid arthritis and 76 healthy controls) participated. In employed healthy people few challenging activities were associated with low IL-6 values. No or rare feelings of overstress, satisfaction with the amount of rest and sleep and a "good" variety of activities were associated with low ACPA values. Healthy non-employed people having enough challenging activities had lower IL-8 and increased ACPA values. Compared to that, different correlations were identified in non-employed people with RA. For example, frequently perceived impact of the health condition on activities, less ability to adapt activities to changed living conditions and little or no variety of activities were associated with increased CRP values. The figure shows one example of the associations between CRP values and the ability to adapt activities in people with RA. Conclusions: In the present study statistically significant differences of employed and non-employed people with RA and healthy controls were found. Hence, we suggest considering employment status, impact of the health condition on activities, variety of activities and abilities to adapt activities when targeting occupational balance in the treatment of people with RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3207